Aplicação de um teste de convergência condicional para estados brasileiros - Limaverde, Luciana Vasconcelos Brandão (2010)
This work investigates, through econometric tests, the occurrence of income convergence among Brazilian States for the period between 1985 and 2006. Despite being the study of conditional ß-convergence, it includes the analysis of σ- convergence, necessary to obtain conclusive data on the occurrence of convergence. The collected data used in the research were provided from official agencies of brazilian States. They are composed by values of GDP (Gross Domestic Product), of the survey about the time of average schooling of persons aged 25 years or more and of Gini and Theil coefficients. The methodology adopted was a crosssection regression with a dummy for the North and Northeast regions, because of the relevance of statistical data which separates the profile of growth trend of these regions from the others. The economic growth model suggested by Barro and Sala-i- Martin is used to the econometric tests. An educational variable supported by the broad doctrine as an important guideline of economic growth is added to the regression of ß-convergence. The conclusion, according to the econometric tests results, is that the hypothesis of convergence occurs. It is based on verification of conditional income ß-convergence and σ-convergence in Brazilian states. Therefore, it is confirmed the tendency of poorer economies, located in North and Northeast regions grow more rapidly toward its steady-state in comparison with the richest ones and the tendency of all of them achieve a level of common development.